2008
DOI: 10.1007/s00705-008-0235-2
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and genome organization of a member of a new and distinct Caulimovirus species from dahlia

Abstract: A distinct caulimovirus, associated with dahlia mosaic, was cloned and sequenced. The caulimovirus, tentatively designated as dahlia common mosaic virus (DCMV), had a double-stranded DNA genome of ca. 8 kb. The genome organization of DCMV was found to be typical of members of the genus Caulimovirus and consisted of six major open reading frames (ORFs), ORFs I-VI, and one minor ORF, ORF VII. Sequence comparisons with the DNA genomes of two known caulimoviruses isolated from dahlia, Dahlia mosaic virus (DMV) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…, 2008), these two new caulimoviruses showed significant sequence divergence compared to that of DMV (Pahalawatta et al. , 2008b; Pappu et al. , 2008).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…, 2008), these two new caulimoviruses showed significant sequence divergence compared to that of DMV (Pahalawatta et al. , 2008b; Pappu et al. , 2008).…”
Section: Introductionmentioning
confidence: 92%
“…Tentatively referred to as Dahlia common mosaic virus (DCMV) and DMV‐D10 (Pahalawatta et al. , 2007; Pappu et al. , 2008), these two new caulimoviruses showed significant sequence divergence compared to that of DMV (Pahalawatta et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMV is a member of the genus Caulimovirus family Caulimoviridae. In addition to DMV, which was characterized at the molecular level (Richins and Shepherd, 1983), recent studies have revealed the presence of at least two more caulimoviruses, tentatively referred to as DMV-D10 and Dahlia common mosaic virus (DCMV) (Nicolaisen, 2003;Pahalawatta et al, 2008a;Pappu et al, 2008). DMV-D10 shares limited sequence similarity with known caulimoviruses, including DMV, although the genome organization clearly suggests that it is a member of Caulimovirus (Pahalawatta et al, 2008a).…”
mentioning
confidence: 99%
“…Moreover, Pahalawatta et al (2008b) reported that the genome of DMV-D10 is integrated into the dahlia genome and the virus exists as an endogenous plant pararetroviral sequence (EPRV). DCMV was found to be a distinct caulimovirus species based on sequence relationships with known caulimoviruses (Pappu et al, 2008).…”
mentioning
confidence: 99%